2021
DOI: 10.3389/fmicb.2021.680854
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Non-selected Intermolecular Gene Conversion in the Polyploid Haloarchaeon Haloferax volcanii

Abstract: Gene conversion is defined as the non-reciprocal transfer of genetic information from one site to a homologous, but not identical site of the genome. In prokaryotes, gene conversion can increase the variance of sequences, like in antigenic variation, but can also lead to a homogenization of sequences, like in the concerted evolution of multigene families. In contrast to these intramolecular mechanisms, the intermolecular gene conversion in polyploid prokaryotes, which leads to the equalization of the multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The observation that anchor genes in the syntenic blocks linked to rho were mapped to both the MRCA of Poaceae and subsequent backbone nodes of the grass phylogeny suggested that, following the rho event, the sequences of the paralogues of an ingroup (such as the core Poaceae) became more similar to each other, relative to sequences of earlier divergent lineage(s) (such as Anomochlooideae). This could be due to gene conversion (also referred to as nonreciprocal exchange), which copies the sequence of one homologue to replace the sequence of another during meiosis (and, to a lesser extent, during the mitotic cell cycle) and can lead to equalization of different gene copies 49 . Indeed, analyses of diploid and allopolyploid cottons ( Gossypium ) supported gene conversion between homologous sequences from past WGD 50 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation that anchor genes in the syntenic blocks linked to rho were mapped to both the MRCA of Poaceae and subsequent backbone nodes of the grass phylogeny suggested that, following the rho event, the sequences of the paralogues of an ingroup (such as the core Poaceae) became more similar to each other, relative to sequences of earlier divergent lineage(s) (such as Anomochlooideae). This could be due to gene conversion (also referred to as nonreciprocal exchange), which copies the sequence of one homologue to replace the sequence of another during meiosis (and, to a lesser extent, during the mitotic cell cycle) and can lead to equalization of different gene copies 49 . Indeed, analyses of diploid and allopolyploid cottons ( Gossypium ) supported gene conversion between homologous sequences from past WGD 50 .…”
Section: Resultsmentioning
confidence: 99%
“…30 ). The mapping of some GDs to a later node could be due to gene conversion, which can lead to equalization of different gene copies 49 . Gene conversions occur frequently in meiosis and has been hypothesized to play a key role in promoting polyploidy-dependent establishment of mutational robustness in plants 92 .…”
Section: Discussionmentioning
confidence: 99%
“…The latter opinion was obtained with genetic approaches, e.g., the generation of homozygous mutants or the way mutations segregated were taken as genetic proof for monoploidy [ 37 , 39 ]. However, since then, it has become clear that at least two polyploid prokaryotes, the methanogenic archaeon Methanococcus maripaludis and the haloarchaeon H. volcani , exhibit highly efficient gene conversion [ 8 , 65 , 66 ]. Gene conversion equalizes homologous, but nonidentical gene copies [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of sexual reproduction, gene conversion can help offset the accumulation of deleterious mutations in asexual organisms (Muller’s Ratchet) (38). Gene conversion has been observed in other polyploid archaea, including M. maripaludis (55 genome copies) and Haloferix volcanii (20 genome copies) (28, 39, 40). M. acetivorans contains up to 17 genome copies when growing with methanol (28), the condition used in this study.…”
Section: Discussionmentioning
confidence: 99%